A review on Black-Scholes model in pricing warrants in Bursa Malaysia - Indra Gunawan, Nur Izzaty Ilmiah; Ibrahim, Siti Nur Iqmal; Abdul Rahim, Norhuda (AIP Publishing, 2016)
This paper studies the accuracy of the Black-Scholes (BS) model and the dilution-adjusted Black-Scholes (DABS) model to pricing some warrants traded in the Malaysian market. Mean Absolute Error (MAE) and Mean Absolute Percentage Error (MAPE) are used to compare the two models. Results show that the DABS model is more accurate than the BS model for the selected data.